The Effect of Using Music in Developing a Child's Sensory Memory (Journal of the College of Basic Education, 2026)
The study in the first chapter addressed the research problem, which highlighted understanding the impact of employing music on the development of the child's sensory and educational abilities. It then discussed the importance and objectives of the research, as well as defining key terms.The second chapter (theoretical framework) introduced the concept of the effect of music on young children, highlighting several free and structured activities, including auditory activities, sound games, and singing, such as physical activities, referring to teaching children music from ages 3-6 years. It reviewed the psychological dimension, the social dimension, and the educational dimension, noting that musical activities can be a means of educating the child in language learning through rhythm and melodic words. It also emphasized the importance of music in a child's life as an expressive artistic activity to which children respond in various ways. The earliest manifestations of this form of expression in a child appear when rhythm blends with the vocal sounds produced.Chapter three dealt with the research procedures, which included children's music and the ways children show their love for music, and then the aspects of a child's natural musical readiness. Chapter four came in explaining the results and conclusions reached by the researcher, followed by the suggestions and recommendations, and the list of sources and references.